Toll-like receptors 7 and 8 mRNA in monocytes of Egyptian children with chronic hepatitis C infection genotype 4 as predictor to "response" interferon and ribavirin treatment - Mohammed A. Khedr; Hatem A. Kanswa; Magdy A. Saber; Tawfik M. Abdel-Motilb (SpringerOpen, 2016)
Background: The contribution of the host immune response to sustained virologic response (SVR) is not clear in children with chronic hepatitis C (CHC). It is still unknown whether TLRs 7&8 expression in monocytes is related to disease progression in HCV infected children or whether it represents a protective factor in those patients who are slow disease-progressors. Objective: The aim of this study was to assess the value of expression of TLRs 7&8 and TNF as a predictor for the outcome of antiviral therapy in children with CHC. Patients and methods: This prospective study included fifty CHC children aged 5-18 years. Thirty-four were males, sixteen were females who received Peg-IFN-α-2b and RBV for 48 weeks. mRNA levels of TLRs 7&8 in monocytes were evaluated using real-time PCR before a 48-week treatment with Peg-IFN-α-2b and RBV. In addition, we studied tumor necrosis factor (TNF) production in monocytes using three-color immunofluorescence and flow cytometry after TLRs 7&8 ligand Resiquimod (R848) stimulation. Results: According to the virological response of the treatment, the infected children were classified into sustained virological response (SVR) 72% and non-responder 28%. The study determined that mRNA levels of TLRs 7&8 were significantly high in SVR compared to non-responders. Furthermore, after stimulation with R848 the median fluorescence intensity (MFI) for TNF protein was significantly high in SVR compared to non-responders. Conclusions: TLRs 7&8 and TNF have great importance in controlling HCV infection and the responses to IFN therapy. Further research covering other stages of CHC at large numbers and at different monocytes subsets levels will be needed.